Interpreting Greek tragedy: myth, poetry, text - Segal, Charles (Cornell University Press, 2019)
Frontmatter -- Contents -- Preface -- Acknowledgments -- Abbreviations -- I. GREEK TRAGEDY: MYTH AND STRUCTURE -- 1. Greek Tragedy and Society: A Structuralist Perspective -- 2. Greek Myth as a Semiotic and Structural System and the Problem of Tragedy -- 3. Greek Tragedy: Writing, Truth, and the Representation of the Self -- II. SOPHOCLES -- 4. Visual Symbolism and Visual Effects in Sophocles -- 5. Sophocles' Praise of Man and the Conflicts of the Antigone -- III. EURIPIDES -- 6. The Tragedy of the Hippolytus: The Waters of Ocean and the Untouched Meadow -- 7. The Two Worlds of Euripides' Helen -- 8. Pentheus and Hippolytus on the Couch and on the Grid: Psychoanalytic and Structuralist Readings of Greek Tragedy -- 9. Euripides' Bacchae: The Language of the Self and the Language of the Mysteries -- IV. TRANSFORMATIONS -- 10. Boundary Violation and the Landscape of the Self in Senecan Tragedy -- 11. Tragedy, Corporeality, and the Texture of Language: Matricide in the Three Electra Plays -- 12. Literature and Interpretation: Conventions, History, and Universals -- Index